2007
DOI: 10.1021/ie070991q
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Horizontal Slug Flow in Pneumatic Conveying

Abstract: Dense-phase pneumatic transportation of bulk materials in the form of slug flow has become a very important technology in industry. In order to understand the underlying mechanisms of slug flow, this paper presents a numerical study of slug flow in horizontal pneumatic conveying by means of discrete particle simulation. To be computationally efficient, the motion of discrete particles is three-dimensional and the flow of continuum gas is two-dimensional, and periodic boundary conditions are applied to both gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…Figure 10b also shows that the radial gas velocity remains negative near the slug tail, but positive near the slug head, as observed in other studies. 58 Different from the velocity distribution, the pressure drop mainly happens inside the slug along the pipe, and is negligible outside the slug (Figure 10d), similar to that observed by Tomita et al 73 Because of the aforementioned flow properties of gas phase, the fluid-drag force shown in Figure 10f, and the pressure gradient force shown in Figure 10g, is both several times the particle gravity force inside the slug and less than particle gravity force inside the settled layers and other parts. Interestingly, it is found that the pressure gradient force has a more uniform distribution in the radial direction than the fluid-drag force, similar to those found in a vertical slug flow.…”
Section: Force Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 10b also shows that the radial gas velocity remains negative near the slug tail, but positive near the slug head, as observed in other studies. 58 Different from the velocity distribution, the pressure drop mainly happens inside the slug along the pipe, and is negligible outside the slug (Figure 10d), similar to that observed by Tomita et al 73 Because of the aforementioned flow properties of gas phase, the fluid-drag force shown in Figure 10f, and the pressure gradient force shown in Figure 10g, is both several times the particle gravity force inside the slug and less than particle gravity force inside the settled layers and other parts. Interestingly, it is found that the pressure gradient force has a more uniform distribution in the radial direction than the fluid-drag force, similar to those found in a vertical slug flow.…”
Section: Force Analysismentioning
confidence: 97%
“…Actually, particles in the back settled layer gradually settle down when the slug moves away. For comparison, the particle-particle force, as the driving force of a slug for picking up particles in its front settled layers, 58 is given in Figure 10h. It can be seen that the particle-particle force is mainly distributed near the middle section of the slug, and can be a thousand times the particle gravity force.…”
Section: Force Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship is used by a number of DEM force models, 15,16 which differ in their treatment of dissipative and tangential forces. Unlike the linear model, the mathematical expression of the Hertzian force depends on the physical properties of the particle.…”
Section: Contact Forcesmentioning
confidence: 99%
“…Morikawa (1982, 1984) studied a gas-solid flow in a horizontal and vertical pipe using different types of relatively large polystyrene spheres. Numerical modeling of pneumatic conveying of solid particles in horizontal tubes has been published by several authors (Kuang et al, 2008;Lain et al, 2009;Sommerfeld and Lain, 2009), but experimental work is still needed to determine pressure drop curves.…”
Section: Introductionmentioning
confidence: 99%